(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the clinical efficacy and safety of intravesical botulinum neurotoxin-A injection in patients with refractory overactive bladder to conservative treatment and anti-muscarinic drugs.Material and Methods: The data of 62 patients, who received botulinum neurotoxin-A (BonTA) injection (100 U) for overactive bladder (OAB) between 2015 and 2019, were reviewed retrospectively. For 55 patients included into the study, the urinary frequency and urgency, the number of incontinence and nocturia episodes, the maximum flow rate (Qmax), the post-void residual volume (PVR), and the Urinary Incontinence Quality of Life (I-QoL) scores were evaluated before the treatment and at the third month after the treatment. Results: The comparison of the pre-treatment and posttreatment 3rd-month follow-up data revealed a statistically significant decrease in the urinary frequency and urgency, and the number of incontinence and nocturia episodes (p 0.05). The mean I-QoL score increased significantly in the posttreatment 3rd month compared to the pre-treatment scores (43.62 ± 11.2 and 75.2 ± 12.6, p = 0.001, respectively). After the treatment, hematuria developed in 3 female and 2 male patients and urinary tract infections developed in 4 females and 2 male patients.Conclusion: BonTA injection significantly improves the daily urinary frequency, incontinence, and quality of life scores in patients with OAB.